Effect of mindfulness on treatment motivation in patients with substance use disorder - Tanrıkulu, Ali Baran; Kayaoğlu, Kübra (Journal of Dependence, 2024)
Objective: This research aimed to assess the mindfulness levels among individuals with substance use disorder (SUD) and investigate its influence on treatment motivation.Method: A descriptive and cross-sectional study was carried out involving 184 SUD patients. Data collection utilized a Personal Information Form, The Mindful Attention Awareness Scale (MAAS), and the Treatment Motivation Questionnaire (TMQ).Results: A strong positive correlation was identified between MAAS and TMQ levels (r: 0.796, p
Keywords: Mindfulness; motivation; substance use disorder; treatment